Concentric Spherical Representation for Omnidirectional Soft Shadow. (5th April 2013) - Xiao, Yi; Leung, Chi Sing; Ho, Tze Yui; Wan, Liang; Wong, Tien Tsing
<x xml:space="preserve">Abstract</x> Soft shadows play an important role in photo‐realistic rendering. Although there are many efficient soft shadow algorithms, most of them focus on the one‐side light source situation, where a planar light source is on the outside of the scene. In fact, in many situations, such as games, light sources are omnidirectional. They may be surrounded by a number of 3D objects. This paper proposes a soft shadow algorithm for the omnidirectional situation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>